George Speaks - "Smith, Dick King" (Puffin Books: London, 1988)
A story about George, a baby who learns to speak at the unusually early age of 4 weeks. He and his sister try to keep this a secret from the rest of the family, but their parents find out and, on his first birthday, he decides to make his maiden speech to the rest of the assembled family.